The effect of weathering on surface characteristics of chemically modified scots pine (pinus sylvestris) wood - Amanah, Sinta; Martha, Resa; Basri, Efrida; Mubarok, Mahdi; Sekartining Rahayu, Istie; Alipraja, Irsan; Darmawan, Wayan; Gérardin, Phillippe; Emmerich, Lukas; Militz, Holger; Hani Abdullah, Ummi (Pulp and Paper Research Institute, 2024)
Scots pine (Pinus sylvestris L.) sapwood of 200×20×80 mm3(L×R×T) was treated with both cell wall filling and lumen filling chemical agents (low-molecular phenol-formaldehyde, bio-oil, N-methylol/N-methyl compounds, sorbitol-citric acid, polysiloxane), which were fixed inside the wooden structure during heat-curing processes. The present study investigated the impact of the appointed chemical modifications on the surface characteristics of wood, which was addressed by measurements of the surface roughness (Ra), surface free energy (SFE), contact angles, wettability and its bonding quality. Independent of the chemical agents applied, Ra decreased as result of the chemical treatments, while SFE experienced a reduction. The Ra and SFE of both untreated and modified pine specimens increased after weathering processes. The weathering was appointed to cause a decrease in the equilibrium contact angle (θe) and an increase in the constant contact angle change rate (K-value). Increasing K-values after weathering for both untreated and modified pine specimens indicated their better wettability. Increasing wettability after weathering led to better adherence of acrylic paints on the surface of the Scots pine wood. In summary, the chemical modifications decreased the Ra and SFE of the pine sapwood, which may as a consequence affect the wettability and bonding quality of wood during outdoor exposure.